1994
DOI: 10.1088/0268-1242/9/12/003
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise in quantum point contacts

Abstract: The kinetics of electron transport in quantum point contacts has been studied by means of low-frequency noise spectroscopy. The temperature and frequency (Lorentzian or l / f ) dependences of the noise intensity are found to be device specific, in contrast to the conductance dependence, which universally exhibits a strong quantum size effect at low temperatures. The origin of the Lorentzian noise spectrum is electron trapping and release at a single trap close to the point contact, and is connected to random r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
21
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 32 publications
2
21
1
Order By: Relevance
“…Charge noise has been studied both locally by monitoring conductance fluctuations in a quantum point contact (QPC) or quantum dot [7,8,9,10,11,12,13,14,15,16], and on a macroscopic scale using resistance fluctuations in Hall bar structures [16,17,18]. Several charge switching sites have been proposed, either near the 2DEG [9,10,11] or in the remote impurity layer [8,16,17] and more specifically the DX centers [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Charge noise has been studied both locally by monitoring conductance fluctuations in a quantum point contact (QPC) or quantum dot [7,8,9,10,11,12,13,14,15,16], and on a macroscopic scale using resistance fluctuations in Hall bar structures [16,17,18]. Several charge switching sites have been proposed, either near the 2DEG [9,10,11] or in the remote impurity layer [8,16,17] and more specifically the DX centers [13].…”
mentioning
confidence: 99%
“…Several charge switching sites have been proposed, either near the 2DEG [9,10,11] or in the remote impurity layer [8,16,17] and more specifically the DX centers [13]. The charge switching process has been attributed to electron hopping between trap and 2DEG [9,10,11], electrons leaking from the split gates through the Schottky barrier [12,15] or (thermally activated) switching between different sites or configurations within the impurity layer [8,13,16,17]. Trapping of 2DEG carriers can be excluded as the dominant mechanism since 2DEG density fluctuations are too small [16,17].…”
mentioning
confidence: 99%
“…21 The noise spectrum of I QPC in the amplifier bandwidth was dominated by a 1/f contribution, as seen in previous studies on similar QPC devices where the 1/f noise was shown to be due to an ensemble of two-level fluctuators (TLFs). 18 As discussed later, discrete time-domain jumps in I QPC due to the action of single TLFs 18,22 were also occasionally seen. To ensure high detection fidelity in the presence of the constant 1/f noise spectrum, we reference the QPC current (I N / ÀN for small N) to a second current I Z .…”
mentioning
confidence: 86%
“…Electrons can be loaded with fast voltage waveforms, as used in high-speed pumping experiments 5,8 and then probed on millisecond time-scales required for high-fidelity readout. We use a 2-stage measurement protocol to suppress the effect of 1/f noise in the QPC due to non-equilibrium charged defects, 18 and we achieve a sufficiently high charge detection fidelity (probability of the charge detection yielding the right answer for N), to probe loading probabilities at the 10 À6 level. Finally, we demonstrate good qualitative agreement between electron-detection measurements of N, and hni extracted from the pumped current measured in a separate experiment.…”
mentioning
confidence: 99%
“…The RTS noise has been studied in sub-micrometer Si metal-oxide-semiconductor structures [15], AlGaAs/GaAs narrow channels [16], and quantum dots [17]. A higher sample resistance in general restricts the lower frequency range that can be measured.…”
mentioning
confidence: 99%